Convergence or divergence of the European Union's energy strategy in the Central European countries? - Grażyna Wojtkowska-Łodej; Honorata Nyga-Łukaszewska (CES Working Papers, 2019)
Even though there is no common energy policy, EU energy strategy sets the background of the energy landscape in Europe. EU energy policy responds to different challenges in the energy market. One of them is climate change. Growing emissions of greenhouse gases aroused world's interest aimed at reducing the harmful impact of the energy industry on the environment. The European Union has undertaken a low-emission strategy set out in the package called "3x20". The aim of the study is on one hand to present program measures and regulations taken in the EU in the recent period for sustainable energy management and reduction of greenhouse gas emissions and on the other try to assess program's implementation by Member States. The article presents the current state in terms of achieving the objectives of the "3x20" package in 2017, with a special diagnosis of conditions and trends in the Central and Eastern Europe countries that joined the EU after 2004.Paper includes the analysis of the official EU documents within energy policy and empirical evidence on their implementation. The analysis uses the literature review and data from the Passport, Eurostat and OECD databases. Methods employed in this study include critical literature review and secondary data analysis.
Keywords: 330; low-carbon economy; Central and Eastern Europe; climate policy